The Role of Billionaires in the Economic Paradigm of the 21st Century - TOME, Eduardo (Management Dynamics in the Knowledge Economy, 2017)
The purpose of this paper is to analyses the importance of billionaires in the economy of the 21st century. We assume that rich people and organizations existed since civilization exists, but billionaires are a different phenomenon and they appear within a very specific context. This paper analyses the cause of the existence of billionaires and also discusses some consequences of that existence. The methodology of the paper is basically a search of data and information online coupled with reasoning about the topic. We conclude that, quite crucially, billionaires are a distinctive feature of the economy of the 21st century, both by the facts which cause them and the consequences that derive from the billionaires’ existence. Moreover, all those causes and consequences thrive and are related to the knowledge economy. The study is original because even if the top 1% persons have been studied recently, no systematic analysis of causes and effects of billionaires nor the relation with the knowledge economy has been done. The conclusions of the paper matter for politicians, analysts, the billionaires themselves, and all those that live in the knowledge economy. The paper is a limited effort but it defines decisive questions for the world’s future.